Physiological regulation mechanism of multi-chemicals on water transport and use efficiency in soil-maize system. (20th January 2018) - Liao, Renkuan; Zhang, Lilizhong; Yang, Peiling; Wu, Wenyong; Zhang, Zhicheng
Abstract: Currently, functional chemicals, such as superabsorbent polymer (SAP) and fulvic acid (FA) are commonly employed combined to enhance the utilization ability of crop to soil water in dry-land areas, which promoted greatly the sustainable development of dry-land agriculture. However, the serious insufficiency of study on regulation mechanism of multi-chemicals combined application restricts its future development. In this paper, an ingenious experiment was designed to explore the regulation mechanism of combined effects of SAP and FA on water transport and use efficiency in soil-maize system. By thorough analysis, the main indexes, i.e., root length density (RLD), root nitrogen mass density (RNMD) and stomatal conductance (SC) were determined. The regulation mechanism gradually became clear after making the relationships between the above mentioned indexes and the endogenous hormones (ABA, ZR, GA and IAA) of maize. It has been seen that SAP enhanced the rate of root water uptake (RWU) but FA reduced the RWU to a certain extent. Nevertheless, it still showed an increased trend by 16.5% on an average for RWU when SAP and FA applied combined to maize. Moreover, a potential theory could be summarized that, root growth was regulated by ABA, ABA/(ZR+GA+IAA), and stomatal conductance was regulated by ZR, ZR/ABA. Thus it revealed that multi-chemicals stimulated the release of the endogenous hormones mentioned above in crops ensuring effective utilization of soil water and inhibited the rate of transpiration to reduce soil water loss.